Chicken IgY reduces the risk of Pseudomonas aeruginosa urinary tract infections in a murine model - Schwartz, Franziska A.; Christophersen, Lars; Thomsen, Kim; Baekdal, Sarah; Pals Bendixen, Maria; Jørgensen, Mette; Bull Rasmussen, Ida Kirstine; Laulund, Anne Sofie; Høiby, Niels; Moser, Claus (Frontiers in Microbiology, 2022)
Introduction: Urinary tract infections (UTI) with Pseudomonas aeruginosa are a severe problem in disposed patients in modern healthcare. P. aeruginosa establishes recalcitrant biofilm infections and can develop antibiotic resistance. Gargling with avian egg yolk anti-Pseudomonas antibodies (IgY) has shown clinical effect in preventing onset of chronic P. aeruginosa lung infections in patients with cystic fibrosis. Therefore, we speculated whether passive intravesically administered IgY immunotherapy could be a novel strategy against P. aeruginosa UTIs. Aim: To evaluate if prophylactic repurposing of anti-Pseudomonas IgY can prevent UTIs with P. aeruginosa in a UTI mouse model. Methods: In vitro, P. aeruginosa (PAO1 and PAO3) was mixed with increasing concentrations of specific anti-Pseudomonas IgY (sIgY) or non-specific control IgY (cIgY) and/or freshly isolated human neutrophils. Bacterial growth was evaluated by the optical density at 600 nm. In vivo, via a temporary transurethral catheter, 10-week-old female Balb/c mice were intravesically infected with 50 ml of a bacterial suspension and sIgY, cIgY, or isotonic NaCl. IgY and NaCl were either co-installed with the bacteria, or installed prophylactically, 30 minutes prior to infection. The animals were euthanized 20 hours after infection. Vesical bacteriology was quantified, and cytokine expression in the bladder homogenate was measured by multiplex cytokine assay. Results: In vitro, sIgY concentrations above 2.5% reduced bacterial growth in a dose-dependent manner. In vivo, a UTI lasting for minimum 7 days was established by installing 5· 106 CFU of P. aeruginosa PAO1. sIgY reduced vesical bacterial load if co-installed with P. aeruginosa PAO1. Prophylactic sIgY and cIgY reduced bacterial load when compared to isotonic NaCl. CXCL2 and G-CSF were both increased in infected bladders compared to non-infected controls which had non-detectable levels. Co-installation of sIgY and bacteria nearly completely inhibited the inflammatory response. However, the cytokine levels in the bladder did not change after prophylactic administration of sIgY or cIgY. Conclusions: Prophylactic sIgY significantly reduces the risk of developing UTI in a mouse model of P. aeruginosa cystitis. and may serve as a novel non-antibiotic strategy in preventing P. aeruginosa UTIs.